(untitled) (Comparative Professional Pedagogy, 2021)
The article offers a brief overview of the structure and main areas of development in the Chinese education system. The transition period in China’s education system can be characterized by the following slogan: “On the way to modernization, world and future”. Indeed, systemic reforms pave the way in which the state’s policy is playing a guiding role and schools and universities a leading role in the gradual search for special Chinese ways of education development. The focus of the article is mainly on the types of education in China and the conditions for obtaining education (preschool, primary, secondary, upper secondary and postgraduate education). Besides, it is crucial to consider the structure of vocational education, which is implemented in the following types: primary, secondary, higher vocational education and vocational training. Moreover, the article describes the features and forms of education for children with special needs as an important part of general education. Emphasis is placed on the level and conditions of higher and postgraduate education in China (bachelor’s, master’s, doctoral degrees). It must be noted that the article highlights several specialized projects and comprehensive plans in the field of education aimed at reforming and improving the status of education, including “Project No 211” and “Project No 985”. It also outlines the main milestones of “The Implementation Plan” and “The Plan until the Year of 2035”, as well as the measures taken to realize many other goals despite the COVID-19 pandemic. Particular attention is paid to the support provided by the Chinese government to the education system during the COVID-19 pandemic. It has affected all its levels to not allow the educational process to become radically different and manage to strengthen in the global crisis. Finally, the article addresses several controversial issues in China’s education sector, including reforming the system of education quality assessment and reformatting private education.